Circles around the sun : in search of a lost brother - McCloskey, Molly, 1964- (Overlook Press, 2012)
When Molly McCloskey was a young girl, her brother Mike, 14 years her senior, started showing signs of paranoid schizophrenia. Through reading an astonishing archive of letters preserved by her mother and grandmother, and interviewing old friends of Mike's, she began to piece together a picture of his life.